MENGOPTIMALKAN KUALITAS KESEHATAN NEONATUS MELALUI PEMBERDAYAAN MASYARAKAT DAN KOMUNIKASI ANTAR STAKEHOLDER - ANAFRIN YUGISTYOWATI (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
Neonatal mortality rates indicates the level of health development in country and the quality of life of its people. The high mortality of children in the age of up to one year, which is one third occurs in the first month after birth and about 80 percent of neonatal deaths occur in the first week. This is because the mother's condition before and during pregnancy will determine the condition of the baby.Neonatal mortality is a very important thing that must be considered by policy makers. This condition requires an effort to promote health and empowerment through integrated communication between stakeholders. Development communication here plays a role in bridging empowerment programs according to community needs supported by local resources. Through the implementation of integrated communication it is hoped that it can encourage the public to be aware of the importance of the neonatal critical period at the age of 0 to 28 days in carrying out good and correct management of young baby care.